Impact of bottle size on in‐home consumption of wine: a randomized controlled cross‐over trial. (8th April 2020) - Codling, Saphsa; Mantzari, Eleni; Sexton, Olivia; Fuller, Georgia; Pechey, Rachel; Hollands, Gareth J.; Pilling, Mark; Marteau, Theresa M.
Abstract: Aim: To assess the impact of purchasing wine in 50 cl bottles compared with 75 cl bottles on the amount of wine consumed at home. Design: Cross‐over randomized controlled trial with a 'usual behaviour' period of a maximum of 3 weeks between conditions. Setting: Households in the United Kingdom. Participants: One hundred and eighty‐six households that consumed between two and eight 75 cl bottles of wine each week. Intervention: Households were randomized to the order in which they purchased wine in two bottle sizes. During two 14‐day intervention periods, households purchased a pre‐set volume of wine—based on their baseline self‐reported weekly consumption—in either 75 cl bottles or 50 cl bottles. On days 7 and 14 of each study period, participating households sent photographs of each purchased wine bottle. Measurements: The primary outcome was the volume of study wine in millilitres (ml) consumed during each study period estimated through returned photographs. The secondary outcome was the rate of consumption measured by the mean number of days taken to drink 1.5 litres from each bottle size. Findings: One hundred and sixty‐six of 186 enrolled households satisfactorily completed the study. After accounting for pre‐specified covariates, 191.1 ml [95% confidence interval (CI) = 42.03–339.2] or 4.5% (95% CI = 1.0–7.9%) more wine was consumed per 14‐day period from 75‐cl bottles than from 50‐cl bottles. Consumption was 5.8% faster (95% CI = –10.9 to –0.4%) from 75 cl bottles than from 50 cl bottles. Conclusions: Consuming wine at home from 50 cl bottles, compared with 75 cl bottles, may reduce both amount consumed and rate of consumption.